1993
DOI: 10.1021/ac00071a003
|View full text |Cite
|
Sign up to set email alerts
|

Improved chiral separations of basic compounds in capillary electrophoresis using .beta.-cyclodextrin and tetraalkylammonium reagents

Abstract: Approaches to improve resolution in chiral separation of several basic pharmaceutical compounds by capillary electrophoresis (CE) via a cyclodextrin (CD) inclusion complexation are described. Tetraalkylammonium reagents, including long-chain cationic surfactants and short-chain alkylammonium hydroxides, are examined for controlling the electroosmotic flow in order to improve resolution of the cationic enantiomers. In this regard, short-chain tetraalkylammonium cations (such as tetrabutylammonium and tetramethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 17 publications
1
46
0
Order By: Relevance
“…The validation of this method for the quantitation of isoprenaline aerosol and to the analysis of serum samples spiked norepinephrine and epinephrine was performed. Compared with the previous methods [10][11][12][13][14][15][16][17][18], the merit of this work was used to analyze enantiomers of norepinephrine, epinephrine or isoprinaline in pharmaceutical formulation and human serum. The results indicated the proposed method represents good selectivity, precision and accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The validation of this method for the quantitation of isoprenaline aerosol and to the analysis of serum samples spiked norepinephrine and epinephrine was performed. Compared with the previous methods [10][11][12][13][14][15][16][17][18], the merit of this work was used to analyze enantiomers of norepinephrine, epinephrine or isoprinaline in pharmaceutical formulation and human serum. The results indicated the proposed method represents good selectivity, precision and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Above 30 mM, the enantiomeric separation of NE or EP could not be improved and the migration time increased. Many papers [10,13,20] reported that using dual CD system could obtain higher enantiomeric resolutions. Therefore, in our work, 5 mM of ␤-CD, Me-␤-CD or DM-␤-CD was added to the running buffer containing 30 mM HP-␤-CD, respectively.…”
Section: Effect Of CD Concentration On Enantiomer Separationmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are also in good accordance with the reported experimental data in HPLC 12 or CE. 13,20 It supports that CM-β-CD is a better chiral selector for NA enantiomers comparing with β-CD.…”
Section: Methodsmentioning
confidence: 70%